Molecular Mechanisms of Parturition - F. Ferré (Hindawi Limited, 1997)
The initial signal for triggering human parturition might be fetal but of trophoblastic origin. Concomitantly, this placental signal would have as its target not only the uterus but also the fetus by activating its hypothalamo-pituitary-adrenocortical axis. The latter would represent a second fetal signal which, at the fetomaternal interface, would amplify and define in time the mechanisms responsible for the onset of labor, implying changes in the myometrial and cervical extracellular matrix associated with the accession of the contractile phenotype for myometrial cells. At each phase of these processes in the utero-feto-placental system, the nature of these signals remains to be identified. Is there a single substance, or rather, and more likely, a combination of several?